Intravital NIR-II three-dimensional photoacoustic imaging of biomineralized copper sulfide nanoprobes. Issue 13 (11th March 2021) - Zhou, Hui-Chao; Ren, Jie; Lin, Yuejun; Gao, Duyang; Hu, Dehong; Yin, Tinghui; Qiu, Chen; Miao, Xiaoyan; Liu, Chengbo; Liu, Xin; Zheng, Hairong; Zheng, Rongqin; et al.
Abstract : The systematic application of NIR-II three-dimensional photoacoustic imaging for revealing the behavior of CuS nanoprobes in vivo . Abstract : Photoacoustic (PA) imaging with functional nanoprobes in the second near-infrared region (NIR-II, 1000–1700 nm) has aroused much interest due to its deep tissue penetration and high maximum laser permissible exposure. However, most NIR-II PA imaging is performed using the two-dimensional (2D) imaging modality, which impedes the comprehension of the in vivo biodistribution, angiography and molecular-targeted performance of NIR-II nanoprobes (NPs). Herein, we report the systematic monitoring of biomineralized copper sulfide (CuS) NPs, typical NIR-II NPs, in mouse models by employing NIR-II three-dimensional (3D) PA imaging. The advanced imaging modality provides dynamic information about the 3D biodistribution and metabolic pathway of CuS NPs. We also achieved contrast-enhanced 3D PA imaging of abdominal and cerebral vessels at a high signal-to-background ratio. Moreover, the tumor-targeted CuS NPs conjugated with the bombesin peptide endowed NIR-II 3D PA with superior performance in imaging orthotopic tumors both deep in the prostate and in the brain beneath the intact scalp and skull. Our results highlight the potential of NIR-II 3D PA imaging for the evaluation of the in vivo behavior of NPs, thus providing a promising strategy for screening NPs in clinical translational studies.